An Analysis of Communication Strategies in Speaking Classroom Interaction - Munawaroh, Fita Fitriatul; Imanudin, Jajat (CV. Ridwan Publisher, 2019)
This study investigated on the communication strategies at speaking classroominteraction and dominant communication strategies used by students for speakingclassroom interaction at the eighth grade of MTs Bina Sejahtera Kuningan. Theeight grade of MTs Bina Sejahtera Kuningan was chosen purposively as thesample. A descriptive qualitative methodology was employed in this study, and datawere collected through classroom observation and semistructured interview. Thedata from classroom observation and semi structured-interview were analyzed bytranscribing, redacting data, triangulation and drawing a conclusion. The findingsshowed that there were some types of communication strategies used by students inspeaking classroom interaction, message abandonment, use of fillers, selfrepetition, mime, expressing non-understanding, direct appeal for help, feigningunderstanding, asking for repetition, and asking for clarification. The dominantcommunication strategy used by students at speaking classroom interaction wasSelfRepetition (33,33%), Use ofFiller (24,82%), Direct Appeal For Help (9,93%),Asking For Clarification (7,80%), Message Abandonment (7,09%), Asking ForRepetition (5,67%), Mime (4,26%), and the least number of communicationstrategy used by students was Feigning Understanding (2,84%). Based on thesefindings, it is recommended that the students have to improve their speaking skill,especially in pronouncing, mastery of vocabularies and grammar and in speakingclass, the teacher should use teaching varieties to make students more active inclassroom interaction and overcome students problems and students difficulties inspeaking.Key words: Communication strategies, Descriptive qualitative methodology, Types of communication strategies